Utilizing Blockchain Technology in Various Applications to Secure Data Flows. A Comprehensive Analysis - Halkiopoulos, Constantinos; Antonopoulou, Hera; Kostopoulos, Nikos (Technium: Romanian Journal of Applied Sciences and Technology, 2023)
Blockchain technology has emerged as a disruptive force in the world of digital transactions, with applications across a wide range of industries. This paper provides a comprehensive review of the potential applications of blockchain technology, including finance, healthcare, supply chain management, and voting. The paper discusses the benefits and challenges of using blockchain technology, as well as real-world case studies of its implementation. The paper concludes with suggestions for future research, exploring new applications and addressing the challenges associated with the use of blockchain technology.